Favorable long term effects of intensified immunosuppression combined with therapeutic plasma exchange in patients with early-onset progressive systemic sclerosis-related interstitial lung disease - J. Potjewijd; R. Tobal; D. Silvertand; H.A. Gietema; J.G.M.C. Damoiseaux; P. van Paassen (Journal of Translational Autoimmunity, 2022)
Objective: Systemic sclerosis (SSc) related mortality and morbidity remains high. Immunosuppressive therapy is considered most effective when immune activity and inflammation but not fibrosis still dominates the disease process. This study evaluated long-term intensified immunosuppression combined with therapeutic plasma exchange (TPE) in early-onset progressive SSc-related interstitial lung disease (ILD). Methods: The study cohort consisted of 161 SSc patients, with a median follow-up time of 8.9 years. The standardized mortality rate (SMR) and overall survival was calculated in patients with and without cardiopulmonary involvement. We used a standardized, pragmatic, non-randomized approach to treat 24 consecutive early progressive SSc-ILD patients with intensified immunosuppressive therapy, including plasma exchange. Outcome measurements were event-free survival (EFS), pulmonary function and safety profile. The outcome was compared with the analyzed data from the other SSc-ILD patients, who did not fulfill the inclusion criteria, and instead were treated with estimated optimal care (EOc). Results: The age-adjusted SMR of all 161 SSc patients was 3.0 (CI95%; 0.32–5.68). EFS at 10 years was 49.9% in the intensified treatment group and 43.3% in the EOc group (p = 0.106). Improvement of the percentage of predicted forced vital capacity (%pFVC) and percentage of predicted diffusing capacity for carbon monoxide (%pDLco) in the intensified treatment group was +10.1% respectively +3.6%, compared to a decrease of respectively 10.8% and 7% in the EOc (p < 0.001 resp. p = 0.019). Safety analysis showed 1 death (female patient, over 75 years of age), due to pneumosepsis, in the intensified treatment group. Conclusion: Intensified and long-lasting immunosuppression combined with TPE is safe in early severe systemic sclerosis and is associated with improved EFS and pulmonary function as compared to the outcome in the variable but EOc group. Our findings warrant larger studies for confirmation.